2015
DOI: 10.1210/en.2015-1417
|View full text |Cite
|
Sign up to set email alerts
|

Down, But Not Out: Partial Elimination of Androgen Receptors in the Male Mouse Brain Does Not Affect Androgenic Regulation of Anxiety or HPA Activity

Abstract: We previously found that androgen receptor (AR) activity mediates two effects of T in adult male mice: reduction of anxiety-like behaviors and dampening of the hypothalamic-pituitary-adrenal response to stress. To determine whether brain ARs mediate these effects, we used the Cre/loxP technology seeking to disable AR throughout the central nervous system (CNS). Female mice carrying the floxed AR allele (ARlox) were crossed with males carrying cre recombinase transgene controlled by the nestin promoter (NesCre)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…The CeL may be the activation site necessary for the beneficial effects of testosterone on extinction, as CeL neuronal activity was increased during extinction recall only in the acute experiment, which is where we observed the enhanced extinction memory. These data seem to be consistent with other findings that report that androgen receptors in the medial prefrontal cortex or hippocampus (where we also found no effects of Lupron) are not necessary for the anxiolytic effects of testosterone ((Chen et al, 2016)).…”
Section: Discussionsupporting
confidence: 93%
“…The CeL may be the activation site necessary for the beneficial effects of testosterone on extinction, as CeL neuronal activity was increased during extinction recall only in the acute experiment, which is where we observed the enhanced extinction memory. These data seem to be consistent with other findings that report that androgen receptors in the medial prefrontal cortex or hippocampus (where we also found no effects of Lupron) are not necessary for the anxiolytic effects of testosterone ((Chen et al, 2016)).…”
Section: Discussionsupporting
confidence: 93%
“…An elevated anxiety-state, in particular during the light phase, was seen in the open field, novel object and elevated plus maze tests, but not in the light/dark box and corticosterone levels remained high after mild stress. In contrast, neural AR invalidation did not affect androgenic regulation of anxiety or HPA activity (Chen et al, 2016;Raskin et al, 2009;Picot et al, 2016). It has been suggested that in neural AR mutant male mice, this lack of effect may be due to residual AR expression in the amygdala and hypothalamus, but not in the hippocampus or cortex (Chen et al, 2016).…”
Section: The Hypothalamic-pituitary-adrenal (Hpa) Axis and Anxiety-rementioning
confidence: 97%
“…This conditional mutation, targeting AR in neuronal and glial precursor cells as early as embryonic day (ED) 10.5, does not interfere with the normal development of the urogenital tract. The same mouse line was generated and reported by other groups (Chen et al, 2016;Juntti et al, 2010;Karlsson et al, 2016). Deletion of the AR gene in neurons was also performed using synapsin-I-Cre transgenic mice (Yu et al, 2013).…”
Section: Genetic Modelsmentioning
confidence: 99%
“…Residual neural AR in Nestin‐ARKO could give rise to false negative conclusions (ie, that the absence of a phenotype indicates the lack of neural androgenic mediation, when it remains possible that sufficient AR remains in neural populations). To the extent to which this has been assessed, there is indeed evidence of significant androgen sensitive neural populations in the nervous system of Nestin‐ARKO mice, including in the amygdala and hypothalamus, and more restricted interpretations of behavioural results are therefore warranted …”
Section: Neural‐specific Models Of Loss Of Functionmentioning
confidence: 99%
“…To the extent to which this has been assessed, there is indeed evidence of significant androgen sensitive neural populations in the nervous system of Nestin-ARKO mice, including in the amygdala and hypothalamus, and more restricted interpretations of behavioural results are therefore warranted. 60…”
Section: Neural-specific Models Of Loss Of Functionmentioning
confidence: 99%